Novel and emerging therapies for B cell lymphoma - Sabarish Ayyappan; Kami Maddocks (Journal of Hematology & Oncology, 2019)
Abstract Lymphomas are a heterogeneous group of lymphoproliferative disorders, with unique clinical and biological characteristics that exhibit variable response to therapy. Advances in chemo-immunotherapy have improved outcomes in a number of lymphoma subtypes; however, the prognosis for many patients with relapsed and refractory disease remains poor. Novel therapies including several small molecule inhibitors and chimeric antigen receptor T cells have been approved for the treatment of different lymphoma subtypes at relapse, changing the therapy landscape and further improving survival in many of these diseases. This has led to a focus on the development of new cellular therapy, antibody-based therapy, and small molecule inhibitors for relapsed and refractory disease that offer an alternative approach to cytotoxic chemotherapy. We will review these promising novel therapies and discuss their safety and efficacy in first in human studies.